Competition Law in Malaysia - Nasarudin Abdul Rahman, Haniff Ahamat (Sweet & Maxwell, 2016)
this book discusses the development and implementation of competition law in Malaysia, looking comprehensively at the powers and function of the competition regulator, and the enforcemenr procedures of malaysian competition law